2020
DOI: 10.3390/microorganisms8060851
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Transmission Outcomes Following Co-Infection of Sheep with Strains of Bluetongue Virus Serotype 1 and 8

Abstract: Bluetongue virus (BTV) causes an economically important disease, bluetongue (BT), in susceptible ruminants and is transmitted primarily by species of Culicoides biting midges (Diptera: Ceratopogonidae). Since 2006, northern Europe has experienced multiple incursions of BTV through a variety of routes of entry, including major outbreaks of strains of BTV serotype 8 (BTV-8) and BTV serotype 1 (BTV-1), which overlapped in distribution within southern Europe. In this paper, we examined the variation in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…Transmission of parental and reassortant strains of BTV from ITI Culicoides to naïve sheep was highly efficient across all five strains of BTV, confirming previous studies (40, 41). Interestingly, severity of clinical infection in sheep was not broadly correlated to the number of infective bites received, but, where very few fully infected C. sonorensis fed, this occasionally led to a late and slowly progressing viraemia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Transmission of parental and reassortant strains of BTV from ITI Culicoides to naïve sheep was highly efficient across all five strains of BTV, confirming previous studies (40, 41). Interestingly, severity of clinical infection in sheep was not broadly correlated to the number of infective bites received, but, where very few fully infected C. sonorensis fed, this occasionally led to a late and slowly progressing viraemia.…”
Section: Discussionsupporting
confidence: 89%
“…The quantity of BTV RNA in blood samples taken from sheep in the first ten days post-infection was tested on the day of collection. Preliminary data suggested that a blood sample with a sqPCR C T value of less than 25 indicated that BTV infection would reach peak viraemia in the sheep within the following two days and this was used as a guide to time blood-feeding of C. sonorensis (40). C. sonorensis were allowed to feed on sheep in card boxes through a fine mesh lid at a density of approximately 250 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that viremia was measured from systemic blood samples after bleeding of sheep in the jugular vein. As pointed out by Veronesi et al, the viral load found in systemic blood could be dissimilar to that found on skin periphery ( 72 ), probably lower if we attend to the work conducted by Melzi et al, in which the concentration of viral RNA in systemic blood was between 100 and 1,000 times higher than that found in skin from day 5 postinfection ( 73 ). Experimental infections have shown that Culicoides infection rates are very low, even when blood-fed on experimentally infected sheep at peak viremia levels ( 72 ).…”
Section: Discussionmentioning
confidence: 64%
“…Studies of infection in C. sonorensis with other viruses (e.g. BTV) have previously demonstrated infections where there was potential both for retention of virus at low and sub-transmissible levels of infection [35]. This can occur through restriction of the virus to the hind mid-gut due to a mesenteron escape barrier and restriction to the fat body due to a hemocoel dissemination barrier [42].…”
Section: Discussionmentioning
confidence: 99%
“…Natural models for the transmission of viruses between ruminants and Culicoides have been used in various studies to explore the transmission of BTV within a controlled and standardized experimental design [34,35] that could greatly facilitate BEFV research. In this study, we investigated the susceptibility to infection of one Culicoides and three mosquito species for BEFV.…”
mentioning
confidence: 99%